2015
DOI: 10.1007/s11105-015-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Salt Tolerance Traits with Different Effects at the Seedling Stage of Bread Wheat

Abstract: We evaluated salt tolerance in 319 recombinant inbred lines derived from a cross between Roshan and Falat (seri82) in bread wheat (Triticum aestivum L.). This study identified quantitative trait lci (QTLs) with additive (a) and additive×additive (aa) epistatic effects, and characterized their salt treatment interactions (at and aat) at the seedling stage. Using a genetic map of 730 DArT and SSR markers, we identified 65 additive QTLs governing 13 traits using the QTL Cartographer program to assess single-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 64 publications
(78 reference statements)
4
29
1
2
Order By: Relevance
“…The variable expressions of these genes are essential components of plant salt stress response and adaptation mechanisms and may be genotype specific and/or transcriptionally regulated by cis-regulatory elements (CREs). Several studies have revealed the association of DNA polymorphisms with ST in wheat (Genc et al 2010; Xu et al 2013; Masoudi et al 2015; Turki et al 2015), but are yet to be elucidated due to lack of functional and molecular validation. The understanding of how potential molecular cues relate to salt stress response remains a major challenge in molecular biology, as transcriptional mechanisms contribute to the regulation of nearly all cellular processes (Li et al 2006; von Korff et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The variable expressions of these genes are essential components of plant salt stress response and adaptation mechanisms and may be genotype specific and/or transcriptionally regulated by cis-regulatory elements (CREs). Several studies have revealed the association of DNA polymorphisms with ST in wheat (Genc et al 2010; Xu et al 2013; Masoudi et al 2015; Turki et al 2015), but are yet to be elucidated due to lack of functional and molecular validation. The understanding of how potential molecular cues relate to salt stress response remains a major challenge in molecular biology, as transcriptional mechanisms contribute to the regulation of nearly all cellular processes (Li et al 2006; von Korff et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Which was supported by Mwadzingeni et al [22] who reported similar correlations between YPP and both BM and GN under drought-stress conditions. QTL clusters and colocalized QTL for grain yield and component traits related to salinity stress have been reported [26,39,[59][60][61]. In addition, an unusually high correlation between agronomic traits controlled by pleiotropic QTL exists [22,26,[60][61][62][63][64].…”
Section: Qtl Clusters For Grain Yield and Related Traits Under Salinimentioning
confidence: 98%
“…QTL clusters and colocalized QTL for grain yield and component traits related to salinity stress have been reported [26,39,[59][60][61]. In addition, an unusually high correlation between agronomic traits controlled by pleiotropic QTL exists [22,26,[60][61][62][63][64]. Two occurrences might be responsible for the co-localization of QTL associated with different traits: rst, genes affecting various traits or the same traits were strongly linked; and second, single gene might have a series of effects on related traits or affect two or more independent traits [62].…”
Section: Qtl Clusters For Grain Yield and Related Traits Under Salinimentioning
confidence: 99%
“…For agronomically important traits, linkage maps are necessary for mapping the QTLs as they are constructed from genotypic data from multiplexed marker assays [32][33][34][35]. High-density linkage maps also offers a genomic resource for positional cloning of significant genes.…”
Section: Qtl Mapping For Abiotic Stressmentioning
confidence: 99%
“…They can also be applied in comparative genomics to assess chromosomal organization and evolution as they are constructed from sequence tagged markers. In the linkage map, markers are helpful in identifying regions having QTLs of selected traits and several QTLs have mapped previously for salt tolerance [36,17,35] and drought tolerance [37][38][39]…”
Section: Qtl Mapping For Abiotic Stressmentioning
confidence: 99%